2022
DOI: 10.3390/jpm12030434
|View full text |Cite
|
Sign up to set email alerts
|

Are Risk Factors for Postoperative Significant Hemorrhage following Total Knee Arthroplasty Potentially Modifiable? A Retrospective Cohort Study

Abstract: Total knee arthroplasty (TKA) is the treatment of choice for end-stage osteoarthritis (OA) of the knee, because it alleviates pain and restores function of the knee. However, TKA-associated hemorrhage and subsequent anemia remain a concern. Most previous studies have defined meaningful postoperative bleeding as blood loss > 500 mL or hemoglobin (Hb) drop > 20 g/L. Therefore, we defined significant hemorrhage as a postoperative Hb drop more than 20 g/L in this study, and we investigated possible risk fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 76 publications
0
5
0
1
Order By: Relevance
“…Total knee arthroplasty (TKA) and total hip arthroplasty (THA) can result in substantial perioperative blood loss, which has been associated with postoperative morbidity and mortality 1-3 . Tranexamic acid (TXA) has been increasingly utilized because of its efficacy in the reduction of blood loss following total joint arthroplasty (TJA) 4,5 .…”
mentioning
confidence: 99%
“…Total knee arthroplasty (TKA) and total hip arthroplasty (THA) can result in substantial perioperative blood loss, which has been associated with postoperative morbidity and mortality 1-3 . Tranexamic acid (TXA) has been increasingly utilized because of its efficacy in the reduction of blood loss following total joint arthroplasty (TJA) 4,5 .…”
mentioning
confidence: 99%
“…THR surgeries are associated with a higher Hb drop due to several factors, most notably osteotomy and excision of a highly vascularized part of bone. Total knee replacement also showed an increase in a study done among knee arthroplasty patients in Taiwan [17], with 3.34 g/dL compared to 2.8 g/dL postoperatively. As reported above, replacement surgeries are expected to have a higher Hb drop as they deal with highly vascularized bone structure and are associated with osteotomies and excisions.…”
Section: Discussionmentioning
confidence: 95%
“…Tere was no signifcant diference (p � 0.08) in mean Hb drop between regional anesthesia and GA even though the mean showed GA having a lower mean compared to regional anesthesia. Tis difered from a study done in Taiwan [17] in a retrospective study that showed patients who underwent spinal anesthesia were less likely to lose blood than patients undergoing GA. Regional anesthesia is more often associated with less blood loss, with the sympathetic nerve blockage causing less blood oozing.…”
Section: Advances In Orthopedicsmentioning
confidence: 99%
“…Additionally, Hart et al showed that simultaneous bilateral TKA had significantly higher rates of transfusion within 72 hours after the surgical procedure at 37.7% compared with unilateral TKA at 10.9% (p < 0.0001) 12 . Furthermore, acute blood loss is a known risk factor for ischemic sequelae such as stroke and myocardial infarction and may be a risk factor for symptomatic pulmonary embolism and venous thromboembolism [30][31][32][33] .…”
Section: Discussionmentioning
confidence: 99%